The lived experience of God in Hebbel’s dramas (§ 1) - Blaustein, Leopold (Phainomena (Ljubljana), 2025)
The text seeks to define the term “lived experience of God” and delineate the scope of investigating this concept in the context of Friedrich Hebbel’s dramas. The meaning of the lived experience of God is established through the lens of intentionality. In a narrow sense, lived experiences of God are those experiences, in which God is the direct and proper intentional object. In a broader sense, lived experiences of God include experiences whose intentional object is not God, but is nonetheless related to God. The experience of God is studied both in its noetic as well as its noematic character.
Keywords: doživljanje Boga; Friedrich Hebbel; intencionalnost; intentionality; lived experience of God; noematic investigation; noematska raziskava; psihologija; psychology